The variability of brightest cluster galaxies at high radio frequencies. Issue 2 (10th November 2021) - Rose, Tom; Edge, Alastair; Kiehlmann, Sebastian; Baek, Junhyun; Chung, Aeree; Jung, Tae-Hyun; Kim, Jae-Woo; Readhead, Anthony C S; Sedgewick, Aidan
ABSTRACT: Variability of a galaxy's core radio source can be a significant consequence of active galactic nucleus accretion. However, this variability has not been well studied, particularly at high radio frequencies. As such, we report on a campaign monitoring the high radio frequency variability of 20 nearby, cool-core brightest cluster galaxies. From our representative sample, we show that most vary significantly on time-scales of approximately 1 yr and longer. Our highest cadence observations are at 15 GHz and are from the Owens Valley Radio Observatory. They have a median time interval of 7 d and mostly span between 8 and 13 yr. We apply a range of variability detection techniques to the sources' light curves to analyse changes on week to decade long time-scales. Most notably, at least half of the sources show 20 per cent peak to trough variability on 3 yr time-scales, while at least a third vary by 60 per cent on 6 yr time-scales. Significant variability, which is important to studies of the Sunyaev–Zel'dovich Effect in the radio/sub-mm, is therefore a common feature of these sources. We also show how the variability relates to spectral properties at frequencies of up to 353 GHz using data from the Korean VLBI network, the NIKA2 instrument of the IRAM 30-m telescope, and the SCUBA-2 instrument of the James Clerk Maxwell Telescope.